Effect of Robot-Assisted Gait Training on Lower Limb Motor Function of Children with Cerebral Palsy： A Meta-Analysis - JIANG Xiaoyu; BI Hongyan; SUN Wenyu; LIU Huifen; SU Hang; JIANG Jiahui (康复学报)
ObjectiveTo evaluate the effect of robot-assisted gait training (RAGT) on lower limb motor function of children with cerebral palsy (CP) by meta-analysis.MethodsData were searched from the Cochrane Library, PubMed, Web of Science, Embase, CNKI, Wanfang Data, VIP and CBMdisc databases. The randomized controlled trials (RCTs) of RAGT on children with CP were included, and the retrieval time was from inception to December 2021. The main outcome measures were GMFM-D and GMFM-E scores of the gross motor function measure (GMFM), Berg balance scale (BBS), functional ambulation category (FAC) scale, walking speed, 6-minute walk test (6MWT), modified Ashworth scale (MAS). Two researchers conducted literature screening, data extraction, quality evaluation and risk assessment independently according to the inclusion and exclusion criteria. RevMan 5.3 software was used for meta-analysis according to the systematic evaluation manual provided by the Cochrane Collaboration Network. The statistical heterogeneity was assessed by probability value (P value) and heterogeneity value (I2 value). If P≥0.1 and I2≤50%, a fixed effects model would be used. If P<0.1 or I2>50%, a random effects model would be used.ResultsA total of 10 RCTs with 390 cases were included, 187 cases in the control group, 203 cases in the experimental group. Meta-analysis showed that, compared with the control group, the GMFM-D score of the experimental group was higher [SMD=0.58, 95% CI (0.29, 0.88), P=0.000 1], the GMFM-E score was higher [SMD=0.47,95% CI (0.18, 0.77), P=0.001], the BBS score was higher [MD=5.85, 95% CI(4.00, 7.70), P<0.000 01], the FAC score was higher [MD=0.57, 95% CI (0.24,0.91), P=0.000 8], the speed of walking was faster [MD=0.06, 95% CI(0.02, 0.10), P=0.009], and 6MWT score was higher [MD=80.18, 95% CI (23.00, 137.36), P=0.006]; there was no significant difference in MAS score between the two groups [MD=-0.10, 95% CI (-0.32, 0.12), P=0.39].ConclusionRAGT can effectively improve lower limb motor functions such as gross motor function, balance function and walking function of children with CP. Due to the limitations of the included studies, high-quality, multicenter and large sample size clinical RCTs are still needed in the further research to provide more reliable evidence.